Effect of Moringa Leaves Podwer Enriched with Royal Jelly on the Anthropometric Measurements of Neonates in Central Sulawesi, Indonesia - Lina Fitriani; Citrakesumasari; Veni Hadju; Sudirman Nasir; Apik Indarty Moedjiono; Masyitha Muis; Nurpudji Astuti Taslim; Sri Sumarmi; M. Bambang Uswatul Firdaus; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Moringa oleifera and Royal Jelly have been studied for their benefits in pregnant women. Our study investigated the non-pharmacological potential of Moringa oleifera enriched with Royal Jelly (MRJ) on newborn anthropometric measurements, including birth weight, birth length, head circumference, and chest circumference, in pregnant women in Central Sulawesi Province, Indonesia. Materials and Methods:This study was a randomized, single-blind, controlled trial involving 160 pregnant women (divided into two groups). The intervention group received two MRJ capsules daily, while the control group consumed one Multi Micronutrient Supplement (MMS) tablet daily. The intervention lasted for six months. Data analysis using SPSS 28 using statistical methods such as Chi-square test, Fisher’s exact test, Kolmogorov-Smirnov, Mann-Whitney, Independent t-test, and ANCOVA. The level of significance is p < 0.05. Results:Most pregnant women in this study were aged 20-25 years, with 139 (86.9%) and 108 (67.5%) multiparous mothers. All variables measured were not significantly different at baseline except maternal BMI (p = 0.31). However, at birth, there was a significant difference in BW (3174.81 ± 396.81 g for the MRJ group vs. 3073.40 ± 477.08 g for the MMS group) and BL (48.96 ± 0.97 cm for the MRJ group vs. 49.23 ± 2.22 cm for the MMS group) (p < 0.05). This study showed that BW was higher in the MRJ group compared to the MMS group. Even after controlling for BMI in the analysis, the MRJ intervention had a significant impact on BW (p < 0.05). In contrast, birth length was more significant in the MMS group than in the MRJ group. Conclusions:This study found that MRJ supplementation during pregnancy resulted in newborn size comparable to MMS, a multinutrient supplement designed to improve newborn anthropometric outcomes. Future studies are needed to refine the supplementation design.